2019
DOI: 10.3389/fendo.2019.00697
|View full text |Cite
|
Sign up to set email alerts
|

Application and Utility of Continuous Glucose Monitoring in Pregnancy: A Systematic Review

Abstract: Background: In the past decade, continuous glucose monitoring (CGM) has been proven to have similar accuracy to self-monitoring of blood glucose (SMBG) and yet provides better therapy optimization and detects trends in glucose values due to higher frequency of testing. Even though the feasibility and utility of CGM has been proven successfully in Type 1 and 2 diabetes, there is a lack of knowledge of its application and effectiveness in pregnancy, especially in gestational diabetes mellitus (GDM). In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 43 publications
1
46
0
3
Order By: Relevance
“… 24 , 36 The CGM may also be beneficial in women with other types of diabetes. A systematic review by Yu et al 37 reported that CGM was superior to SMBG in women with GDM for detecting hypoglycemic and hyperglycemic excursions, which may result in improved maternal and fetal outcomes for CGM users with GDM.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 36 The CGM may also be beneficial in women with other types of diabetes. A systematic review by Yu et al 37 reported that CGM was superior to SMBG in women with GDM for detecting hypoglycemic and hyperglycemic excursions, which may result in improved maternal and fetal outcomes for CGM users with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning pregnancy outcomes, we could not demonstrate that CSII treatment induced a lower incidence of adverse pregnancy events compared with MDI therapy. The studies in this field gave conflicting results and, despite some positive results, most of the studies reported [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al, reported that CGM is able to reduce neonatal hypoglycemia (RR 0·66, 95% CI 0·48 to 0·93; 3 studies, 428 infants) ( 21 ). Latest updated evidence from 2019 by Yu et al suggests that CGM is superior to SMBG among pregnant women with gestational diabetes mellitus as it is able to detect hypoglycemic and hyperglycemic episodes ( 36 ). Therefore, regular monitoring of glucose levels in pregnant women with diabetes through specific glucose monitoring devices could ensure limitation of hypoglycemic episodes and then influence the outcomes for both mother and child.…”
Section: Discussionmentioning
confidence: 99%